2018
DOI: 10.1080/15387216.2019.1573694
|View full text |Cite
|
Sign up to set email alerts
|

Regional integration and the economic geography of Belarus

Abstract: This study presents novel research on the economic geography of Belarus. The 118 regions of Belarus are examined in relation to the Eurasian Customs Union (EACU) through the period 2005-2014. Our estimation methods specifically take spatial and dynamic processes into account. We observe that EACU membership has corresponded to a slowdown in the process of regional economic convergence in Belarus, and intensified economic competition with a geographical dimension among regions. Furthermore, we find some evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…The aforementioned spatial effects are particularly relevant within the context of innovation, growth, and development [66][67][68]. This relevance was theoretically formalised by Ertur and Koch [69], who showed that spatial externalities resulting from the local accumulation of knowledge result in interdependencies among countries.…”
Section: Spatial Econometric Estimation Resultsmentioning
confidence: 98%
“…The aforementioned spatial effects are particularly relevant within the context of innovation, growth, and development [66][67][68]. This relevance was theoretically formalised by Ertur and Koch [69], who showed that spatial externalities resulting from the local accumulation of knowledge result in interdependencies among countries.…”
Section: Spatial Econometric Estimation Resultsmentioning
confidence: 98%
“…Considering the diversity of realities within the European Union integration process (Furkova, 2020), the respective convergence/divergence trends have attracted the attention of several researchers (Olejnik, 2008), to assess the impacts on new member-states (Smetkowski, 2015). However, there are other contexts that have deserved the consideration of academics who have carried out studies related to spatial dynamics, such as those from the following countries: Russia (Balash et al, 2020), Belarus (Celbis et al, 2018), Mexico (German-Soto & Brock, 2015, Romania (Goschin, 2017), China (He et al, 2017), Great Britain (Henley, 2005), Tunisia (Labidi, 2019), the Iberian Peninsula , the United States (Rey & Montouri, 1999), Colombia (Royuela & Adolfo Garcia, 2015) and Brazil (Silveira-Neto & Azzoni, 2006). Spatial autocorrelation approaches have also been considered in other assessments, such as the following: personal insolvency (Bishop, 2013), ripple effect on housing values (de la Paz et al, 2017), technical efficiency (Ezcurra, Iraizoz, & Rapun, 2008), transport infrastructures (Gao et al, 2019), economic growth efficiency with low carbon (Ju & Zhang, 2020), pollutant emissions (Li et al, 2018), food inflation (Liontakis & Kremmydas, 2014), eco-efficiency , rental housing , transport efficiency (Ma, Wang, Sun, Liu, & Li, 2018), sulphur dioxide emissions (Nan et al, 2020), fertility rate (Salvati et al, 2020), homicides and personal damages (Santos-Marquez & Mendez, 2020), interregional migration (Sardadvar & Rocha-Akis, 2016), diabetes incidence/ prevalence (Shrestha et al, 2016), carbon emissions (Su, 2020), educational standards (Tselios, 2008) and energy efficiency (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%